Activation of distinct antiviral T-cell immunity: A comparison of bi- and trispecific T-cell engager antibodies with a chimeric antigen receptor targeting HBV envelope proteins - Debelec-Butuner, Bilge; Quitt, Oliver; Schreiber, Sophia; Momburg, Frank; Wisskirchen, Karin; Protzer, Ulrike (Frontiers in Immunology, 2022)
Abstract Despite the availability of an effective prophylactic vaccine, 820,000 people die annually of hepatitis B virus (HBV)-related liver disease according to WHO. Since current antiviral therapies don’t provide a curative treatment for the 296 million HBV carriers around the globe, novel strategies to cure HBV are urgently needed. A promising approach is the redirection of T cells toward HBV-infected hepatocytes employing chimeric antigen receptors or T-cell engager antibodies. We recently described the effective redirection of T cells employing a second-generation chimeric antigen receptor directed against the envelope protein of hepatitis B virus on the surface of infected cells (S-CAR) as well as bispecific antibodies that activate CD3 or CD28 on T cells employing the identical HBV envelope protein (HBVenv) binder. In this study, we added a trispecific antibody comprising all three moieties to the tool-box. Cytotoxic and non-cytolytic antiviral activities of these bi- and trispecific T-cell engager antibodies were assessed in co-cultures of human PBMC with HBV-positive hepatoma cells, and compared to that of S-CAR grafted T cells. Activation of T cells via the S-CAR or by either a combination of the CD3- and CD28-targeting bispecific antibodies or the trispecific antibody allowed for specific elimination of HBV-positive target cells. While S-CAR-grafted effector T cells displayed faster killing kinetics, combinatory treatment with the bispecific antibodies or single treatment with the trispecific antibody was associated with a more pronounced cytokine release. Clearance of viral antigens and elimination of the HBV persistence form, the covalently closed circular (ccc) DNA, through cytolytic as well as cytokine-mediated activity was observed in all three settings with the combination of bispecific antibodies showing the strongest non-cytolytic, cytokine-mediated antiviral effect. Taken together, we demonstrate that bi- and trispecific T-cell engager antibodies can serve as a potent, off-the-shelf alternative to S-CAR-grafted T cells to cure HBV.